2023
DOI: 10.1088/2053-1591/ace41c
|View full text |Cite
|
Sign up to set email alerts
|

Low energy ion-solid interactions: a quantitative experimental verification of binary collision approximation simulations

Hans Hofsäss,
Felix Junge,
Patrick Kirscht
et al.

Abstract: Ultra-low energy ion implantation has become an attractive method for doping of two-dimensional materials and ultra-thin films. The new dynamic Monte Carlo program IMINTDYN based on the binary collision approximation allows a reliable prediction of low energy implantation profiles and target compositional changes, as well as efficient simulation of high energy light ion scattering. To demonstrate the quality of these predictions and simulations, we present a model case experiment where we implanted W ions into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…For sputtering simulations, "simultaneous weak collisions" have been introduced [40], which add collisions with larger impact parameters to the simulation. Recently, it has been shown that simultaneous weak collisions are also relevant to heavy ion implantation [41]. Lastly, SRIM does not consider dynamic changes to the lattice during implantation.…”
Section: Introductionmentioning
confidence: 99%
“…For sputtering simulations, "simultaneous weak collisions" have been introduced [40], which add collisions with larger impact parameters to the simulation. Recently, it has been shown that simultaneous weak collisions are also relevant to heavy ion implantation [41]. Lastly, SRIM does not consider dynamic changes to the lattice during implantation.…”
Section: Introductionmentioning
confidence: 99%